2012
DOI: 10.2355/isijinternational.52.1066
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Initial Mold Filling with Utilization of Swirl Blades

Abstract: The flow pattern in the uphill teeming process has been found to be closely related to the quality of ingots regarding the formation of non-metallic inclusions and entrapment of mold flux. The filling conditions can be improved by the utilization of a swirl blade in the runner. The emphasis of this study is to investigate the flow pattern of steel in the gating system and molds with swirl blades implemented at the bottom of the vertical runners during the initial stage of the mold filling process based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…This is really expected for the teeming process to lead to a lower initial velocity to the mold and to lower the hump height. [11] In Figure 16, all the swirl numbers are >2 when the flaring angle is <60 deg. This means that there is a strong rotation, since the wall had a weak effect on the liquid steel, i.e.…”
Section: A Validation and Mesh Sensitivitymentioning
confidence: 96%
See 2 more Smart Citations
“…This is really expected for the teeming process to lead to a lower initial velocity to the mold and to lower the hump height. [11] In Figure 16, all the swirl numbers are >2 when the flaring angle is <60 deg. This means that there is a strong rotation, since the wall had a weak effect on the liquid steel, i.e.…”
Section: A Validation and Mesh Sensitivitymentioning
confidence: 96%
“…[10] The direction at which the swirl blade is placed in the vertical runner can also affect the flow pattern, and the use of a swirl blade can decrease and stabilize the wall shear stress. [11] However, a swirl blade is always quite difficult to manufacture, and when it is inserted in the gating system, there is a risk that the runner will be clogged. This may also bring in a new inclusion to the liquid steel before solidification.…”
Section: Haitong Bai Mikael Ersson and Pä R Jö Nssonmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the years, many researchers have investigated this technique by numerical and physical modelling. [5][6][7][8][9][10] When using a swirl blade, there is a risk of introducing new inclusions to the liquid steel due to the high wall shear stress inside the refractory wall. The manufacturing process of the swirl blade is also rather complicated, which reduces its application.…”
Section: An Experimental and Numerical Study Of Swirling Flow Generatmentioning
confidence: 99%
“…24) Furthermore, it has already been used to analyse the swirling flow generated by the swirl blade. [6][7][8][9][10]15) However, some published work simulating the turbulent swirling flow for a gas cyclone 25) and tundish 13,14) found that the Reynolds stress model (RSM) 26) can simulate the swirling flow most accurately compared to the experimental results. The numerical simulation part of this work used all three turbulence models above to test which one that best could describe the swirling flow more precisely, especially for the air-core vortex.…”
Section: Numerical Modelmentioning
confidence: 99%